Implementation of Cooperation Agreement Between the Ministry of Internal Affairs, Police, Attorney General Office (Ago) in Handling and Crime Of Corruption in Indonesia - Cipto Dwi Leksana; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Corruption in Indonesia at this time, is already in a position of very severe and so deeply rooted in every facet of life. The development of corrupt practices from year to year is increasing, both in quantity or amount of losses to the state and in terms of the quality of the increasingly systematic, sophisticated and scope has expanded in all aspects of society. Increased corruption uncontrolled will bring disaster on the lives of not only the national economy but also the life of the nation in general. Rampant corruption cases in Indonesia, no longer know the limits of who, why, and how. Not only office holders and the interests of who committed the crime of corruption both in the public and private sector, but corruption has become a phenomenon. Cooperation Agreement between the Ministry of Internal Affairs, the Attorney General and the Police into a new breakthrough in creating a legal product that provides a form of cooperation among government agencies in combating corruption in Indonesia from all sectors of the country.Keywords: Cooperation Agreement; Crime; Corruption.